2008
DOI: 10.1002/mds.22278
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of123I‐FP‐CIT SPECT in the differential diagnosis of essential tremor and Parkinson's disease in Italy

Abstract: Economic evaluation (Italian NHS perspective) modeling (123)I-FP-CIT SPECT (DaTSCAN) compared to clinical judgment alone for differentiating essential tremor (ET) from Parkinson's Disease (PD). A 5-year Markov model was constructed to assess the cost-effectiveness of (123)I-FP-CIT SPECT to differentiate ET from PD in patients referred to a movement disorder specialist in Italy. Published data and a double-round, Delphi panel of 12 specialists populated the model. Effectiveness was expressed as the projected Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 14 publications
0
69
0
3
Order By: Relevance
“…Meta-analysis confirmed the role of radionuclide imaging in this setting [1] and further cost-effectiveness studies showed the economic benefits of this diagnostic procedure [2,3]. Recently, we read with great interest the paper of Badiavas and colleagues [4] published in your journal.…”
mentioning
confidence: 69%
“…Meta-analysis confirmed the role of radionuclide imaging in this setting [1] and further cost-effectiveness studies showed the economic benefits of this diagnostic procedure [2,3]. Recently, we read with great interest the paper of Badiavas and colleagues [4] published in your journal.…”
mentioning
confidence: 69%
“…Some studies have already focused on this issue. For example, an Italian study reported an overall decrease of costs for the health care system by implementing 123 I-FP-CIT SPECT for differential diagnosis of ET versus IPS, as compared with the conventional diagnostic pathway based on clinical judgment alone (81). Other recent prospective multicentric studies have looked at the impact of 123 I-FP-CIT SPECT on clinically uncertain PS and demonstrated that for the subgroup of patients who underwent the scanning procedure, medication was changed at a significantly earlier time point and there was significantly greater confidence in the diagnosis 4 wk, 12 wk, and 1 y after the initial diagnosis.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Although DAT imaging may be expensive, the cost effectiveness of DAT imaging is reported to be good (49)(50)(51). For example, Van Laere et al (51) analyzed the cost FIGURE 6.…”
Section: Cost Effectiveness Of Dat Imagingmentioning
confidence: 99%